Discovery of a Novel Nav1.7 Inhibitor From Cyriopagopus albostriatus Venom With Potent Analgesic Efficacy - Zhang, Yunxiao; Peng, Dezheng; Huang, Biao; Yang, Qiuchu; Zhang, Qingfeng; Chen, Minzhi; Rong, Mingqiang; Liu, Zhonghua (Frontiers in Pharmacology, 2018)
Spider venoms contain a vast array of bioactive peptides targeting ion channels. A large number of peptides have high potency and selectivity toward sodium channels. Nav1.7 contributes to action potential generation and propagation and participates in pain signaling pathway. In this study, we describe the identification of µ-TRTX-Ca2a (Ca2a), a novel 35-residue peptide from the venom of Vietnam spider Cyriopagopus albostriatus (C. albostriatus) that potently inhibits Nav1.7 (IC50 = 98.1 ± 3.3 nM) with high selectivity against skeletal muscle isoform Nav1.4 (IC50 > 10 µM) and cardiac muscle isoform Nav1.5 (IC50 > 10 µM). Ca2a did not significantly alter the voltage-dependent activation or fast inactivation of Nav1.7, but it hyperpolarized the slow inactivation. Site-directed mutagenesis analysis indicated that Ca2a bound with Nav1.7 at the extracellular S3-S4 linker of domain II. Meanwhile, Ca2a dose-dependently attenuated pain behaviors in rodent models of formalin-induced paw licking, hot plate test and acetic acid-induced writhing. This study indicates that Ca2a is a potential lead molecule for drug development of novel analgesics.